Expression of N-WASP is regulated by HiF1α through the hypoxia response element in the N-WASP promoter - Salvi, Amrita (2017)
Cancer cell migration and invasion involves temporal and spatial regulation of actin cytoskeleton reorganization, which is regulated by the WASP family of proteins such as N-WASP (Neural- Wiskott Aldrich Syndrome Protein). We have previously shown that expression of N-WASP was increased under hypoxic conditions. In order to characterize the regulation of N-WASP expression, we constructed an N-WASP promoter driven GFP reporter construct, N-WASPpro-GFP. Transfection of N-WASPpro-GFP construct and plasmid expressing HiF1α (Hypoxia Inducible factor 1α) enhanced the expression of GFP suggesting that increased expression of N-WASP under hypoxic conditions is mediated by HiF1α. Sequence analysis of the N-WASP promoter revealed the presence of two hypoxia response elements (HREs) characterized by the consensus sequence 5′-GCGTG-3′ at -132 bp(HRE1) and at -662 bp(HRE2) relative to transcription start site (TSS). Site-directed mutagenesis of HRE1(-132) but not HRE2(-662) abolished the HiF1α induced activation of N-WASP promoter. Similarly ChIP assay demonstrated that HiF1α bound to HRE1(-132) but not HRE2(-662) under hypoxic condition. MDA-MB-231 cells but not MDA-MB-231KD cells treated with hypoxia mimicking agent, DMOG showed enhanced gelatin degradation. Similarly MDA-MB-231KD(N-WASPpro-N-WASPR) cells expressing N-WASPR under the transcriptional regulation of WT N-WASPpro but not MDA-MB-231KD(N-WASPproHRE1-N-WASPR) cells expressing N-WASPR under the transcriptional regulation of N-WASPproHRE1 showed enhanced gelatin degradation when treated with DMOG. Thus indicating the importance of N-WASP in hypoxia induced invadopodia formation. Thus, our data demonstrates that hypoxia-induced activation of N-WASP expression is mediated by interaction of HiF1α with the HRE1(-132) and explains the role of N-WASP in hypoxia induced invadopodia formation.